BIMBINGAN KONSELING PERPADUAN ANTARA AGAMA DAN ILMU PENGETAHUAN UNTUK MEMBENTUK KARAKTER DI ABAD 21 - Elfidayati Elfidayati; Alya Zahro Azhari (Pascasarjana UIN Sumatera Utara, 2021)
The implementation of the Indonesian education sector at this time faced several challenges. The stages of learning seem unclear, far from real life. Because of that, it is difficult for students to know the value of learning a subject. This explains that the quality of education in Islamic schools is still very low. This type of research is a qualitative data collection based on a lot of primary and secondary data. The results of this study explain that the contextualization process learning is carried out through integrated learning. Integrated learning can be applied to topics that are discussed from different angles, and what is called a discipline will be interconnected and structured. In addition to building benefits during comprehensive learning, easy experiences are also made. Therefore, students can increase the ability to accept, maintain and implement the concepts learned. So, in this study, it is explained that integrated learning can also help students learn in a complete and meaningful way, not only knowing how to memorize it. Because of that, it is easy for students to use them in everyday life. School research adopts the concept of school nature and applies comprehensive learning for all subjects, which arouses the author's thought to understand the application of comprehensive learning in schools.